The Right to Happiness and its Constitutionalization - Mroziński, Juliusz (Hybris, 2025)
The paper addresses how happiness, traditionally a subjective and philosophical concept, has increasingly become an objective of constitutional frameworks. Through historical, philosophical, and legal analyses, it explores the concept of happiness from its ancient roots in Socratic, Aristotelian, and Kantian philosophy to modern-day implications in constitutional law. The author reviews attempts to juridicize happiness by incorporating it into constitutional preambles and legal principles. Notable case studies include the United States Declaration of Independence, Japan's post-war Constitution, and Korea's Constitution, each of which emphasizes the “pursuit of happiness” as an aspirational rather than a guaranteed right. This distinction underscores ongoing challenges: defining happiness in legal terms and addressing its universal versus individualistic dimensions, particularly in the context of Western democratic frameworks. The analysis suggests a tension between the idealistic aspirations of happiness as a right and the pragmatic limitations of law in fulfilling such abstract ideals.